Investigation of Elastic Properties of Multiaxial Warp Knitted Bandages - (:unkn) unknown (Elsevier Ltd, 2010)
The production of technical textiles is an expanding market. New production methods have also been developed for technical textiles rather than the classical production methods. It is now possible to produce a very wide spectrum of fabric structures in warp knitting technology.Bamboo and soyabean fibres are relatively new regenerated fibres and have special properties, they are also used in medical applications because of their anti-bacterial properties. In this study bandages from Soyabean/Polyester/Elastomeric yarn and Bamboo/Polypropylene/Elastomeric yarn bandages were produced by using multiaxial warp knitting method. Multiaxial bandages were tested in terms of tensile strength, elongation and elastic properties. © 2010 Woodhead Publishing Limited. All rights reserved.